PERSEPSI PETANI TERHADAP PERAN KELEMBAGAAN PENYULUHAN SISTEM INTEGRASI SAPI-KELAPA SAWIT (SISKA) DIKABUPATEN INDRAGIRI HULU - Ridudi Yoresta; Susy Edwina; Evy Maharani (Indonesian Journal of Agricultural Economics, 2016)
This study aims to identify institutions and to know the perception of oil palm farmer’s for institutional support Integration System of Oil Palm Cattle Programs (SISKA) in Indragiri Hulu. Methods of data collection using survey methods. The population in this study were farmer’s who applied this SISKA Program and farmer’s are no longer valid SISKA this program. Samples of this technique is 57 people, including respondents who applied and did not apply this SISKA program. Data analysis used descriptive methods. Variables characteristic role of extension were analyzed using Likert Scale. Results shows that the role of Institutional Extension Support (SISKA) by indicator of education with quite a role category, dissemination or innovation information in quite a role category, facilitation in of quite arole category, consultancy in quite a role category, supervision or coaching quite a role category, monitoring and evaluation in quite a role category. The farmer’s perceptions of the SISKA program on the role of education institutions in Indragiri Hulu obtained with quite a role category.